COVID-19 vaccine hesitancy and response to a simple educational intervention in patients attending an outpatient dialysis unit in Johannesburg, South Africa - Cassimjee, Zaheera; Davies, Malcolm; Dayal, Chandni; Chiba, Sheetal (African Journal of Nephrology, 2022)
Background: Patients living with kidney failure are at risk of severe COVID-19 disease. However, vaccination reduces transmission and severity of disease. The uptake of COVID-19 vaccination in South Africa remains poor, suggesting a requirement for novel recruitment strategies. We examined COVID-19 vaccine hesitancy in an urban dialysis population in Johannesburg, South Africa, and investigated the efficacy of an educational intervention on vaccination intention. Methods: One hundred and four participants were recruited from outpatient haemo- and peritoneal dialysis units at the Helen Joseph Hospital. Participants completed anonymous, self-administered questionnaires analysing their acceptance of and concerns regarding COVID-19 vaccination before and after dissemination of the South African Nephrology Society SARS-CoV-2 vaccine information brochure. Results: Seventy-two participants (69%) were unvaccinated against SARS-CoV-2; 23 (22%) indicated unwillingness to undergo vaccination. Vaccine side effects, safety and perceived risk of SARS-CoV-2 transmission by vaccination were important factors in hesitancy. A small proportion believed that COVID-19 was not a serious threat to personal health. News media was an important information source for vaccine-hesitant respondents; prior healthcare worker counselling reduced hesitancy (OR 0.175, 95% CI 0.039–0.784; P = 0.023). The information brochure reduced concerns about vaccine side effects (P = 0.028), increasing vaccination intention to 84%. In-centre vaccination was additionally identified as a strategy to reduce hesitancy (OR 0.053, 95% CI 0.012–0.221; P < 0.001). Conclusions: This first analysis in an urban dialysis population in South Africa highlights factors contributing to vaccine hesitancy. Simple educational interventions capitalising on trust in healthcare workers and improved vaccine accessibility may increase vaccine uptake.